The Impact of Entrepreneurial Intention on Marketing Innovation within the Context of Economic Recessions - Civelek, Mehmet; Fialova, Vendula; Folvarcna, Andrea; Vavrecka, Vladimir; Cervinka, Michal (Transformations In Business & Economics, 2025)
Since economic crises affect individuals’ attitudes to take actions under the conditions of tough economic conditions, they can also influence individuals’ entrepreneurial intention which in turn lead to changes in marketing innovation activities of businesses. In this regard, the purpose of this study is to investigate the effect of entrepreneurial intention on marketing innovation within the context of economic recessions. While entrepreneurial intention is based on the Theory of Planned Behavior, marketing innovation is a dynamic capability included in Resource-based View. The researchers create an online questionnaire and send it to purposively selected respondents from 1367 enterprises in several European countries. Furthermore, the researchers employ Ordinal Logistic Regression Test for analysis purposes. The results confirm the positive impacts of entrepreneurial intention on enterprises’ marketing innovation during the periods of economic recessions. Financial and moral support of family members and previous failures of executives might be the reasons of these findings.